Molecular characterization of a novel β-defensin isoform from the red-toothed trigger fish, Odonus niger (Ruppel, 1836) - S. Neelima (Journal of Genetic Engineering and Biotechnology, 2021)
Abstract Background The concern regarding a post-antibiotic era with increasing drug resistance by pathogens imposes the need to discover alternatives for existing antibiotics. Antimicrobial peptides (AMPs) with their versatile therapeutic properties are a group of promising molecules with curative potentials. These evolutionarily conserved molecules play important roles in the innate immune system of several organisms. The β-defensins are a group of cysteine rich cationic antimicrobial peptides that play an important role in the innate immune system by their antimicrobial activity against the invading pathogens. The present study deals with a novel β-defensin isoform from the red-toothed trigger fish, Odonus niger. Total RNA was isolated from the gills, cDNA was synthesized and the β-defensin isoform obtained by polymerase chain reaction was cloned and subjected to structural and functional characterization in silico. Results A β-defensin isoform could be detected from the gill mRNA of red-toothed trigger fish, Odonus niger. The cDNA encoded a 63 amino acid peptide, β-defensin, with a 20 amino acid signal sequence followed by 43 amino acid cationic mature peptide (On-Def) having a molecular weight of 5.214 kDa and theoretical pI of 8.89. On-Def possessed six highly conserved cysteine residues forming disulfide bonds between C1–C5, C2–C4, and C3–C6, typical of β-defensins. An anionic pro-region was observed prior to the β-defensin domain within the mature peptide. Clustal alignment and phylogenetic analyses revealed On-Def as a group 2 β-defensin. Furthermore, it shared some structural similarities and functional motifs with β-defensins from other organisms. On-Def was predicted to be non-hemolytic with anti-bacterial, anti-viral, anti-fungal, anti-cancer, and immunomodulatory potential. Conclusion On-Def is the first report of a β-defensin from the red-toothed trigger fish, Odonus niger. The antimicrobial profile showed the potential for further studies as a suitable candidate for antimicrobial peptide therapeutics.